Proof of Fermat’s Last Theorem when it is already proven for the exponent n=3 - Kader, Syed Abdul (Journal of Bangladesh Academy of Sciences, 2025)
Pythagorean triples have been known for a long time. Fermat's last theorem sets the limit of any two integers summing up to the third, all raised to the same power, which, according to the theorem, can never be more than 2. After centuries of effort and waiting, Andrew Wiles provided a large and complicated proof of this theorem; this article provides an elementary one. Mathematical subject classification: 11D41, 11D45. J. Bangladesh Acad. Sci. 49(1); 31-33: June 2025